The Downhill Braked Railway Wheel Structural Analysis by Means of the ANSYS Multiphysics Program System Package - Suchánek, Andrej; Harušinec, Jozef (Manufacturing Technology Journal, 2015)
Article deals with the detection of reduced stress in a braked railway wheel based on thermal transient analysis on virtual models, because they influence the characteristics of the railway wheels. Structural analysis was performed by means of the ANSYS Multiphysics program system package. Thermal transient analysis deals with the detection of temperature fields which are result of braking by brake block. The applied heat flux represents the heat generated by friction of brake block. It is applied to the quarter model because of the acceleration calculation. This analysis simulates two braking with subsequent by cooling. Distribution of the equivalent stress was detected in the cross section railway wheel, at selected points. The input parameters were used from the thermal transient analysis. These equivalent stresses result due to thermal load.
Keywords: railway wheel; brake block; residual stress; transient thermal analysis